Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

A Meta‐Regression of 18 Wildfire Chronosequences Reveals Key Environmental Drivers and Knowledge Gaps in the Boreal Nitrogen Balance - Stefan F. Hupperts; Frank Berninger; Han Y. H. Chen; Nicole Fenton; Mélanie Jean; Kajar Köster; Markku Larjavaara; Michelle C. Mack; Marie‐Charlotte Nilsson; Marjo Palviainen; Anatoly Prokushkin; Jukka Pumpanen; et al. (Global Change Biology, 2025)
Climate change has increased the size and frequency of wildfires across the boreal biome. Severe wildfires in boreal forests have been found to trigger shifts from evergreen to deciduous canopies, which has cascading effects on carbon and nitrogen cycling. Ecosystem productivity and carbon uptake in boreal forests are strongly linked with nitrogen, and Earth system models increasingly depend on our understanding of the nitrogen balance to predict post‐fire carbon uptake. To investigate the post‐fire boreal nitrogen balance, we combined a mass balance approach and literature synthesis to estimate rates of nitrogen accumulation and nitrogen inputs across a network of 18 boreal wildfire chronosequences that varied in both wildfire regime and post‐fire canopy type, comprising 527 forest stands. We found that deciduous‐ or mixed‐dominance boreal forests establishing after severe, stand‐replacing fires had the highest nitrogen accumulation rates (15.7 ± 3.8 kg ha −1 year −1 ), while evergreen‐dominated forests establishing after surface‐ or mixed‐severity fires had the lowest nitrogen accumulation rates (1.4 ± 1.1 kg ha −1 year −1 ). Annual known inputs from nitrogen deposition and biological nitrogen fixation combined, estimated from published data, largely failed to explain the rate of nitrogen accumulation, particularly in deciduous or mixed‐dominance forests establishing after stand‐replacing fires, suggesting that the origins of most nitrogen in these forest types remain poorly understood. As the frequency of severe wildfires increases across the boreal biome and shifts toward deciduous canopies become more common, our study reveals a large knowledge gap in the resulting nitrogen balance that needs to be resolved in order to improve predictions of forest carbon uptake.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

A bibliometric analysis of the toxicity research of carbon nanomaterials - M. Han; Y. Lei; F. X. Yang; H. F. Sun (International Journal of Environmental Science and Technology, 2024)

Optimization of A2O–MBR–BAF–O3 combination process for domestic wastewater - L. Huang; J. Han; G. Wang; Y. Hou; Z. Li; F. Yi (International Journal of Environmental Science and Technology, 2023)

Functional traits explain waterbirds' host status, subtype richness, and community‐level infection risk for avian influenza - Shenglai Yin; Ning Li; Wenjie Xu; Daniel J. Becker; Willem F. de Boer; Chi Xu; Taej Mundkur; Nicholas M. Fountain‐Jones; Chunlin Li; Guan‐zhu Han; Qiang Wu; Diann J. Prosser; et al. (Ecology Letters, 2023)
Species functional traits can influence pathogen transmission processes, and consequently affect species' host status, pathogen diversity, and community‐level infection risk. We here investigated, for 143 European waterbird species, effects of functional traits on host status and pathogen diversity (subtype richness) for avian influenza virus at species level. We then explored the association between functional diversity and HPAI H5Nx occurrence at the community level for 2016/17 and 2021/22 epidemics in Europe. We found that both host status and subtype richness were shaped by several traits, such as diet guild and dispersal ability, and that the community‐weighted means of these traits were also correlated with community‐level risk of H5Nx occurrence. Moreover, functional divergence was negatively associated with H5Nx occurrence, indicating that functional diversity can reduce infection risk. Our findings highlight the value of integrating trait‐based ecology into the framework of diversity–disease relationship, and provide new insights for HPAI prediction and prevention.

Paleocurrent and paleowind direction reconstruction research progress and perspectives: a review - F. Y. Zhao; C. L. Hu; C. C. Han; Y. Q. Dong; Q. X. Yuan (Australian Journal of Earth Sciences, 2023)

An assessment model for mapping the susceptibility of deposits accumulation on insulators driven by remotely sensed data - G. Wen; G. Han; F. Zhou; L. Shen; Y. Ma; G. Qian; H. Pan; P. Kong; J. Luo (International Journal of Environmental Science and Technology, 2023)

Mechanical properties and fracture evolution process of Beishan granite under tensile state - C. S. Wang; J. F. Liu; Y. W. Zhao; S. J. Han (Bulletin of Engineering Geology and the Environment, 2022)

A New Berberine Preparation Protects Pancreatic Islet Cells from Apoptosis Mediated by Inhibition of Phospholipase A2/p38 MAPK Pathway - X. J. Bi; Y. Q. Lv; X. H. Yang; Y. Ge; H. Han; J. S. Feng; M. Zhang; L. Chen; M. Z. Xu; F. Y. Guan (Bulletin of Experimental Biology and Medicine, 2022)

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Light grazing facilitates carbon accumulation in subsoil in Chinese grasslands: A meta‐analysis - Zhi‐Yun Jiang; Zhong‐Min Hu; Derrick Y. F. Lai; Dao‐Rui Han; Mei Wang; Min Liu; Meng Zhang; Ming‐Yan Guo (Global Change Biology, 2020)
Grazing by livestock greatly affects the soil carbon (C) cycle in grassland ecosystems. However, the effects of grazing at different intensities and durations on the dynamics of soil C in its subsoil layers are not clearly understood. Here, we compiled data from 78 sites (in total 122 published studies) to examine the effects of varying grazing intensities and durations on soil C content at different depths for grasslands in China. Our meta‐analysis revealed that grazing led to an overall decrease in soil C content and productivity of above‐ground vegetation (e.g., above‐ground biomass and litter) but an increase in below‐ground biomass. Specifically, the effects of grazing on soil C content became less negative or even positive with increasing soil depths. An increase of soil C content was consequently found under light grazing (LG), although soil C content still decreased under moderate and heavy grazing. The increase in soil C content under LG could be largely attributed to the increase of soil C content in subsoil layers (>20 cm), despite that soil C content in surface soil layer (0–20 cm) decreased. Moreover, the magnitude of increase in soil C content under LG in subsoil layers increased with grazing duration. A possible reason of the increase in soil C content in the subsoil layers was due to the increases in below‐ground biomass. Our study highlights that LG may modify the allocation of C input and promote its accumulation in subsoil layers, thus offsetting the negative impact of grazing on surface soil C content, a finding that has significant implications for C sequestration in grasslands.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Global photosynthetic capacity is optimized to the environment - Nicholas G. Smith; Trevor F. Keenan; I. Colin Prentice; Han Wang; Ian J. Wright; Ülo Niinemets; Kristine Y. Crous; Tomas F. Domingues; Rossella Guerrieri; F. Yoko Ishida; Jens Kattge; Eric L. Kruger; et al. (Ecology Letters, 2019)

A hybrid proline-rich cell-wall protein gene JsPRP1 from Juglans sigillata Dode confers both biotic and abiotic stresses in transgenic tobacco plants - D. Q. Liu; Q. Han; T. Shah; C. Y. Chen; Q. Wang; B. F. Tang; F. Ge (Trees, 2018)

Removal of Cr(VI) and phenol coupled with the reduction of sulfate by sulfate-reducing bacteria sludge - X. Han; T.-X. Zhou; S.-W. Xu; Y. Li; Y.-F. Wang; Y. Liu (International Journal of Environmental Science and Technology, 2017)

Microstructure and Ultrastructure Alterations in the Pallium of Immature Mice Exposed to Cadmium - X. F. Yang; Q. G. Han; D. Y. Liu; H. T. Zhang; G. Y. Fan; J. Y. Ma; Z. L. Wang (Biological Trace Element Research, 2016)

Experimental Investigation on Mechanical Behavior and Permeability Evolution of a Porous Limestone Under Compression - B. Han; S. Y. Xie; J. F. Shao (Rock Mechanics and Rock Engineering, 2016)

Efficacy of oral moxifloxacin for aerobic vaginitis - C. Wang; C. Han; N. Geng; A. Fan; Y. Wang; Y. Yue; H. Zhang; F. Xue (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Isolation and characterization of two VpYABBY genes from wild Chinese Vitis pseudoreticulata - J. Xiang; R. Q. Liu; T. M. Li; L. J. Han; Y. Zou; T. F. Xu; J. Y. Wei; Y. J. Wang; Y. Xu (Protoplasma, 2013)

Study of chloropropanols in soy sauce by gas chromatography-triple quadrupole mass spectrometry with coupled column separation without derivatisation - X.-M. Xu; H.-W. Wu; H.-L. He; B.-F. Huang; J.-L. Han; Y.-P. Ren (Food Additives & Contaminants: Part A, 2013)

Choice of microsatellite markers for identifying homozygosity of mitotic gynogenetic diploids in Japanese flounder Paralichthys olivaceus - Y. X. Liu; H. Z. Han; Q. L. Wang; L. Jiang; S. L. Wang; X. Y. Zhang; Y. Liu; Y. F. Wang; Y. J. Liu; H. J. Liu (Journal of Fish Biology, 2013)
A set of 72 microsatellite markers distributed evenly among 24 linkage groups were selected from the published genetic linkage maps of Japanese flounder Paralichthys olivaceus . In two normal diploid full‐sib families, the test for Mendelian inheritance showed that genotypic segregation deviations were not significant at all analysed loci. To estimate microsatellite‐centromere map distances, four meiotic gynogenetic diploid lines were produced by the activation of eggs using UV irradiated sperm of red seabream Pagrus major and cold‐shock treatment to block the extrusion of the second polar body. Under the assumption of complete interference, 21 markers were located in the centromeric region, 39 in the telomeric region and the rest in the intermediate region of linkage groups. A total of 192 mitotic gynogenetic diploids from one spawn were identified by these markers. Genotype analysis showed that the number of homozygous individuals decreased as microsatellite‐centromere map distance increased on each linkage group.

Prolonged exclusive breastfeeding, autumn birth and increased gestational age are associated with lower risk of fever in children with hand, foot, and mouth disease - Q. Zhu; Y. Li; N. Li; Q. Han; Z. Liu; Z. Li; J. Qiu; G. Zhang; F. Li; N. Tian (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Case report: a p.C618S RET proto-oncogene germline mutation in a large Chinese pedigree with familial medullary thyroid carcinoma - X.-P. Qi; R.-B. Ying; J.-M. Ma; W.-T. Liu; Z.-F. Du; J. Fei; C.-P. Yang; Q.-Z. Song; H.-Y. Jin; Z.-G. Chen; J.-S. Han; J.-Q. Wang; et al. (Familial Cancer, 2012)

Is understory plant species diversity driven by resource quantity or resource heterogeneity? - Samuel F. Bartels; Han Y. H. Chen (Ecology, 2010)
What maintains plant species diversity has been the subject of much debate with no general consensus. In forest ecosystems in which understory plants account for the majority of floristic diversity, a crucial question is whether understory plant diversity is driven by resource quantity or resource heterogeneity. This study sought to reconcile the two hypotheses in relation to their effects on understory plant diversity in forest ecosystems. A database of studies that investigated the effects of resources on understory plant diversity was compiled and analyzed using log‐linear models. Whether resource quantity or resource heterogeneity is the determinant of understory plant diversity in individual studies was dependent on stand successional stage(s), presence or absence of intermediate disturbance, and forest biome within which the studies were conducted. Resource quantity was found to govern species diversity in both young and mature stands, whereas resource heterogeneity dominated in old‐growth stands. Resource quantity remained the important driver in both disturbed and undisturbed forests, but resource heterogeneity played an important role in disturbed forests. We argue that neither resource quantity nor heterogeneity alone structures species diversity in forest ecosystems, but rather their influences on understory plant diversity vary with stand development and disturbances in forest ecosystems.

Analysis of genetic structure and relationship among nine indigenous Chinese chicken populations by the Structure program - H. F. Li; W. Han; Y. F. Zhu; J. T. Shu; X. Y. Zhang; K. W. Chen (Journal of Genetics, 2009)

Identification of a recombinant dengue virus type 1 with 3 recombination regions in natural populations in Guangdong province, China - S.-P. Chen; M. Yu; T. Jiang; Y.-Q. Deng; C.-F. Qin; J.-F. Han; E.-D. Qin (Archives of Virology, 2008)

Surveying sandy deserts and desertified lands in north‐western China by remote sensing - C. Z. Yan; T. Wang; Z. W. Han; Y. F. Qie (International Journal of Remote Sensing, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Cross-bridge kinetics of fast and slow fibres of cat jaw and limb muscles: correlations with myosin subunit composition - Joseph F. Y. Hoh; Zhao-Bo Li; Han Qin; Michael K. H. Hsu; Gunther H. Rossmanith (Journal of Muscle Research and Cell Motility, 2007)

Effect of Cadmium in Feed on Organs and Meat Colour of Growing Pigs - Y.-J. Tu; X.-Y. Han; Z.-R. Xu; Y.-Z. Wang; W.-F. Li (Veterinary Research Communications, 2007)

Spectral reflectance and leaf internal structure changes of barley plants due to phytoextraction of zinc and cadmium - B. B. Maruthi Sridhar; F. X. Han; S. V. Diehl; D. L. Monts; Y. Su (International Journal of Remote Sensing, 2007)

Monitoring the effects of arsenic and chromium accumulation in Chinese brake fern ( Pteris vittata ) - Maruthi B. B. Sridhar; F. X. Han; S. V. Diehl; D. L. Monts; Y. Su (International Journal of Remote Sensing, 2007)

Extent and pattern of DNA methylation alteration in rice lines derived from introgressive hybridization of rice and Zizania latifolia Griseb - Z. Y. Dong; Y. M. Wang; Z. J. Zhang; Y. Shen; X. Y. Lin; X. F. Ou; F. P. Han; B. Liu (Theoretical and Applied Genetics, 2006)

Interactions Between High pH and Iron Supply on Nodulation and Iron Nutrition of Lupinus albus L. Genotypes Differing in Sensitivity to Iron Deficiency - C. Tang; S. J. Zheng; Y. F. Qiao; G. H. Wang; X. Z. Han (Plant and Soil, 2006)

Arsenic, Cadmium, Chromium, Cobalt, and Copper in Different Types of Chinese Tea - W.-Y. Han; Y.-Z. Shi; L.-F. Ma; J.-Y. Ruan (Bulletin of Environmental Contamination and Toxicology, 2005)

Phosphorus characteristics correlate with soil fertility of albic luvisols - X. Z. Han; C. Tang; C. Y. Song; S. Y. Wang; Y. F. Qiao (Plant and Soil, 2005)

Decoding the Decoding Region: Analysis of Eukaryotic Release Factor (eRF1) Stop Codon-Binding Residues - Han Liang; Jonathan Y. Wong; Qing Bao; Andre R.O. Cavalcanti; Laura F. Landweber (Journal of Molecular Evolution, 2005)

Effects of Acid Precipitation and Aluminum on Carbohydrate Metabolism in Mycorrhizae of Pinus massioniana - J. K. Tan; F. X. Kong; H. S. Cao; Y. Yu; X. B. Han (Bulletin of Environmental Contamination and Toxicology, 2005)

Activation of a rice endogenous retrotransposon Tos17 in tissue culture is accompanied by cytosine demethylation and causes heritable alteration in methylation pattern of flanking genomic regions - Z. L. Liu; F. P. Han; M. Tan; X. H. Shan; Y. Z. Dong; X. Z. Wang; G. Fedak; S. Hao; Bao Liu (Theoretical and Applied Genetics, 2004)

Arsenic Accumulation and Acute Toxicity in Aquacultural Juvenile Milkfish ( Chanos chanos ) from Blackfoot Disease Area in Taiwan - M.-C. Lin; H.-H. Cheng; H.-Y. Lin; Y.-C. Chen; Y.-P. Chen; G.-P. Chang-Chien; Y.-H. Chou; C.-M. Liao; C.-F. Dai; B.-C. Han; C.-W. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

An Assessment of the RAIM Performance of a Combined Galileo/GPS Navigation System Using the Marginally Detectable Errors (MDE) Algorithm - W. Y. Ochieng; K. F. Sheridan; K. Sauer; X. Han; P. A. Cross; S. Lannelongue; N. Ammour; K. Petit (GPS Solutions, 2002)

An integrated genetic map of Populus deltoides based on amplified fragment length polymorphisms - R. L. Wu; Y. F. Han; J. J. Hu; J. J. Fang; L. Li; M. L. Li; Z. -B. Zeng (Theoretical and Applied Genetics, 2000)

Evidence for Overlapping Substrate Specificity Between Large Neutral Amino Acid (LNAA) and Dipeptide (hPEPTl) Transporters for PD 158473, an NMDA Antagonist - Narayanan Surendran; Kuang-Ming Y. Covitz; Hyo-kyung Han; Wolfgang Sadee; Doo-Man Oh; Gordon L. Amidon; Rufus M. Williamson; Christopher F. Bigge; Barbra H. Stewart (Pharmaceutical Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Interleukin-13 increases prostaglandin E2 (PGE2) production by normal human polymorphonuclear neutrophils by enhancing cyclooxygenase 2 (COX-2) gene expression - C.-L. Yu; M.-H. Huang; Y.-Y. Kung; C.-Y. Tsai; Y.-Y. Tsai; S.-T. Tsai; D.-F. Huang; K.-H. Sun; S.-H. Han; H.-S. Yu (Inflammation Research, 1998)